Cutaneous Pleomorphic Sarcoma: A Forgotten Diagnosis [Sarcoma Pleomórfico Cutáneo, Un Diagnóstico Olvidado] - Fuenzalida-Cruz, H; Loubies-Muñoz, R; Chavez-Rojas, F; Cardemil-Balari, A (Ediciones Doyma, S.L., 2018)
[No abstract available]